Soils to stories: Embedding field insights in research data stewardship - Maina, Priscillah; Kagabo, Desire; Kiogora, Joseline (2025)
Field visit insights provide direct exposure to real-world research environments, illustrating how data is collected, and promoting collaboration between researchers and information professionals. This collaboration helps to identify their evolving information needs throughout every stage of the research lifecycle.